BEYOND THE SCREEN: HOW VIDEO-MEDIATED CULTURAL ENCOUNTERS ACTIVATE HIGHER-ORDER THINKING AND COGNITIVE GROWTH IN EFL LITERATURE CLASSROOMS - Rahayu Kuswardani; Lila Musyahda (Universitas Darussalam Gontor, 2026)
This study examines how video-mediated cultural encounters in an English as a Foreign Language (EFL) literature classroom may support higher-order thinking and cognitive engagement among Indonesian university students. Drawing on Bloom’s Revised Taxonomy and Byram’s model of intercultural communicative competence, it employed a qualitative descriptive design with 33 undergraduate students at a public university in East Java, Indonesia. After viewing two culturally rich short videos, participants answered five open-ended reflection questions. Reflexive thematic analysis indicated that students’ written reflections provided evidence of engagement across all six taxonomic levels, with analyzing and evaluating the most frequently observed. Unlike prior work that relies on textbook or test-item analysis, this study traces higher-order engagement in authentic learner reflections and links it to intercultural awareness. The findings suggest that authentic video content, paired with structured reflective tasks, can serve as a useful catalyst for higher-order engagement and intercultural reflection, although the evidence is interpretive and context-bound.